Waste sorting in Ukraine - Raikov, D. S. (ТДАТУ, 2021)
Ukraininan garbage problem is very harmful for its citizens and in order to solve this problem, first of all, it is necessary to convince our citizens that garbage sorting has numerous advantages. Every Ukrainian should clearly understand its principles. At the same time, it is necessary not only to monitor compliance with the rules for citizen-sorting, but also to encourage them to do it on their own.
Keywords: insufficient waste recycling; environmental pollution